Unmanned roller lateral positioning method for asphalt road construction - Pengju Yue; Xiaohua Xia; Yongbiao Hu; Xuebin Wang; Pengcheng He; Xufang Qin (Scientific Reports)
Abstract Unmanned rollers are typically equipped with satellite-based positioning systems for positional monitoring. However, satellite-based positioning systems may result in unmanned rollers driving out of the specified compaction areas during asphalt road construction, which affects the compaction quality and has potential safety hazards. Additionally, satellite-based positioning systems may encounter signal interference and cannot locate unmanned rollers. To solve this problem, a lateral positioning method for unmanned rollers is proposed to realize the positioning of unmanned rollers relative to asphalt road. First, we captured images from different perspectives and developed a dataset for asphalt road construction. Second, a method for boundary extraction of asphalt road is proposed to accurately locate pixels of asphalt road boundary. Subsequently, the lateral distances are measured by the designed lateral positioning methods. Finally, field validation experiments are conducted to evaluate the effectiveness of the proposed lateral positioning method. The results indicate that the method excels in extracting the asphalt road boundary. Furthermore, the proposed lateral positioning method shows excellent performance, with a mean relative error of 3.40% and a frequency of 6.25 Hz. The proposed lateral positioning method meets the performance requirements for lateral positioning in both accuracy and real-time in asphalt road construction for unmanned rollers.